Exploring topics of the female librarians: Topic modelling approach on research articles - Arumdini, Savira; Ariani, Ria; Santosa, Faizhal Arif (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2024)
Background of the study: Female librarians often face limitations in their professional development and encounter various challenges. Previous studies have shown that while many articles focus on women librarians as a subject, few delve into the topics discussed. Purpose: This research aims to find out which topics are developing in the world of libraries, with a specific focus on female librarians. Method: This study uses topic modelling to explore abstracts from documents discussing female librarians, using BERTopic, scattertext, and VOSviewer to identify emerging topics from data obtained from Scopus. Findings: A total of 6 topics were determined, where Topic 0 and Topic 3 had the highest similarity. At the same time, keyword analysis did not reveal any particularly prominent keywords in the 2020s. Conclusion: The discussion on female librarians covers topics such as professional advancement, work-life balance, knowledge gaps in technology, stereotypes, and the correlation between these topics. This study provides an overview of text analysis that librarians can use to identify topics in a collection of texts, such as abstracts, and examine how different topics relate to each other, as a single document can reflect multiple topics.